Practical completion liquidated damages in construction contracts /Lai Sze Ching - Lai, Sze Ching (2009)
Practical completion is a term widely used in construction contract. However, there is unfortunate there is no firm legally define meaning for the term the court had define it nonetheless there is no single view that is acceptable universally by the court.